2010
DOI: 10.1074/jbc.m109.100222
|View full text |Cite
|
Sign up to set email alerts
|

Liganded Thyroid Hormone Receptor-α Enhances Proliferation of Pancreatic β-Cells

Abstract: Failure of the functional pancreatic ␤-cell mass to expand in response to increased metabolic demand is a hallmark of type 2 diabetes. Lineage tracing studies indicate that replication of existing ␤-cells is important for ␤-cell proliferation in adult animals. In rat pancreatic ␤-cell lines (RIN5F), treatment with 100 nM thyroid hormone (triiodothyronine, T 3 ) enhances cell proliferation. This result suggests that T 3 is required for ␤-cell proliferation or replication. To identify the role of thyroid hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 42 publications
1
55
1
3
Order By: Relevance
“…We have reported that intrapancreatic injection of adenovirus vector that expresses TR␣ leads to the restoration of islet function and an increase in the ␤-cell mass in immunodeficient mice with streptozotocin (STZ)-induced diabetes (15). These results suggest that ligand-bound TR␣ plays a critical role in ␤-cell replication and expansion of the ␤-cell mass during postnatal development.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…We have reported that intrapancreatic injection of adenovirus vector that expresses TR␣ leads to the restoration of islet function and an increase in the ␤-cell mass in immunodeficient mice with streptozotocin (STZ)-induced diabetes (15). These results suggest that ligand-bound TR␣ plays a critical role in ␤-cell replication and expansion of the ␤-cell mass during postnatal development.…”
mentioning
confidence: 69%
“…A single dose of 200 mg/kg STZ was injected intraperitoneally (15,22). Depletion of ␤-cells was confirmed by immunohistochemical staining of the pancreas as well as by detection of severe hyperglycemia.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations